Comparable Initial Engagement of Intracellular Signaling Pathways by Parathyroid Hormone Receptor Ligands Teriparatide, Abaloparatide, and Long‐Acting PTH. (6th May 2021) - Sato, Tadatoshi; Verma, Shiv; Khatri, Ashok; Dean, Thomas; Goransson, Olga; Gardella, Thomas J; Wein, Marc N
ABSTRACT: Multiple analogs of parathyroid hormone, all of which bind to the PTH/PTHrP receptor PTH1R, are used for patients with osteoporosis and hypoparathyroidism. Although ligands such as abaloparatide, teriparatide (hPTH 1‐34 [TPTD]), and long‐acting PTH (LA‐PTH) show distinct biologic effects with respect to skeletal and mineral metabolism endpoints, the mechanistic basis for these clinically‐important differences remains incompletely understood. Previous work has revealed that differential signaling kinetics and receptor conformation engagement between different PTH1R peptide ligands. However, whether such acute membrane proximal differences translate into differences in downstream signaling output remains to be determined. Here, we directly compared short‐term effects of hPTH (1‐34), abaloparatide, and LA‐PTH in multiple cell‐based PTH1R signaling assays. At the time points and ligand concentrations utilized, no significant differences were observed between these three ligands at the level of receptor internalization, β‐arrestin recruitment, intracellular calcium stimulation, and cAMP generation. However, abaloparatide showed significantly quicker PTH1R recycling in washout studies. Downstream of PTH1R‐stimulated cAMP generation, protein kinase A regulates gene expression via effects on salt inducible kinases (SIKs) and their substrates. Consistent with no differences between these ligands on cAMP generation, we observed that hPTH (1‐34), abaloparatide, and LA‐PTH showed comparable effects on SIK2 phosphorylation, SIK substrate dephosphorylation, and downstream gene expression changes. Taken together, these results indicate that these PTH1R peptide agonists engage downstream intracellular signaling pathways to a comparable degree. It is possible that differences observed in vivo in preclinical and clinical models may be related to pharmacokinetic factors. It is also possible that our current in vitro systems are insufficient to perfectly match the complexities of PTH1R signaling in bona fide target cells in bone in vivo. © 2020 American Society for Bone and Mineral Research © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.